Preparation of durian skin nanofibre (DSNF) and its effect on the properties of Polylactic Acid (PLA) Biocomposites - Nur Aimi, M.N.; Anuar, H.; Maizirwan, M.; Sapuan, S.M.; Wahit, M.U.; Zakaria, S. (Universiti Kebangsaan Malaysia, 2015)
Biological fermentation of Rhizopus oryzae was introduced to extract cellulose nanofibre from durian skin fibre (DSF). The diameter of the extracted durian skin nanofibre (DSNF) was in the range of 49-81 nm. The changes of chemical composition of DSNF were clearly seen after evaluated via TAPPI standard test methods. Verification via Fourier transform infrared (FTIR) confirmed the deduction of hemicelluloses and lignin in DSNF in the range of 1200 to 1000 cm-1. X-ray diffraction (XRD) demonstrated increment in the crystallinity from 58.3 to 72.2% after biological fermentation. DSNF was then incorporated into polylactic acid (PLA) via extrusion and injection moulding processes. The effect of 1-5 wt. % DSNF content on PLA biocomposites was investigated for its mechanical and thermal properties. The presence of only 1 wt. % improved the tensile and impact strength by 14.1 MPa and 33.1 kJ/m2, respectively. The thermal properties of PLA-1DSNF biocomposite also recorded higher thermal stability, glass transition temperature (Tg), crystallization temperature (Tc) and melting temperature (Tm). Additionally, from the DMA, it was determined that PLA-1DSNF possessed lower storage modulus and loss modulus, as well as low energy dissipation.